Evaluation of service quality and its impact on customer satisfaction - a life insurance experience - Sirajudeen, M (International Multidisciplinary Research Journal, 2012)
Customer service is the critical success factor in a company and providing top notch customer service differentiates great customer service from indifferent customer service. In the fast paced environment that surrounds industries today, companies find themselves faced with the pressure to discover foolproof ways to manage their businesses. Insurance industry in India is no exception and is undergoing revolutionary changes. Competition has been central to the agenda of companies and it has become one of the enduring themes of our time. The Insurance Industry today is experiencing intense competition and the major players, including LIC have come under pressure. In lieu of this, retaining a Customer is cheaper than finding a new customer. LIC should focus on assurance and empathy to further strengthen the level of satisfaction. Major players in the market especially LIC have to concentrate on retaining existing customers, which could offer huge business potential. Time based competition, quality, product range, timely advertisement, follow up, prompt and error free service are the key ingredients for the better service and it will boost up the sales.